El impacto de las conductas de autocuidado sobre las dimensiones del burnout en psicólogos clínicos iberoamericanos durante la COVID-19 - González-Moreno, Jesús (2024)
Self-care behaviors can be considered a preventive measure for burnout. Therefore, the aim of this paper was to study the relationship of self-care practices with burnout in Ibero-American clinical psychologists who were active during the COVID-19 pandemic. The sample consisted of 160 clinical psychologists (84.4% women) who carried out psychotherapy in different work modalities (i.e., face-to-face, online, mixed). Using different analyses (i.e., structural equation modelling, path analysis, ANOVA), the results indicate that the more self-care behaviors, the lower the levels of burnout. Specifically, self-care behaviors include participating in recreational activities with coworkers, doing physical exercise, maintaining a healthy diet, and considering the physical workspace to be adequate. A greater knowledge of the effect of self-care behaviors on burnout may facilitate the development of good practices that prepare psychologists to face unexpected situations.